A caregiver's perspective on clinically relevant symptoms in behavioural variant frontotemporal dementia: tools for disease management and trial design. Issue 1 (31st October 2022) - Fieldhouse, Jay L.P.; van Dijk, Gaby; Gillissen, Freek; van Engelen, Marie‐Paule E.; de Boer, Sterre C.M.; Dols, Annemiek; van der Waal, Hendrik‐Jan; Regeer, Barbara J.; Vijverberg, Everard G.B.; Pijnenburg, Yolande A.L.
ABSTRACT: Background: Adequate detection of symptoms and disease progression in behavioural variant frontotemporal dementia (bvFTD) is complex. Dementia cohorts usually utilize cognitive and functional measures, which fail to detect dominant behavioural and social cognitive deficits in bvFTD. Moreover, since patients typically have a loss of insight, caregivers are important informants. This is the first qualitative study to investigate caregiver relevant symptoms during the disease course of bvFTD, aiming to improve tools for diagnosis, progression, and future clinical trials. Methods: Informal caregivers of patients in different disease stages of bvFTD ( N  = 20) were recruited from the neurology outpatient clinic of the Amsterdam UMC and a patient organization for peer support in the Netherlands. Their perspectives on clinical relevance were thoroughly explored during individual semi‐structured interviews. Inductive content analysis with open coding was performed by two researchers independently to establish overarching themes and patterns. Results: Caregivers reported a variety of symptoms, in which (i) loss of emotional connection, (ii) preoccupation and restlessness, and (iii) apathy and dependency compose major themes of relevance for diagnosis and treatment. Within heterogeneous disease trajectories, symptom presence differed between stages and among individuals, which is relevant in the context of progression and outcome measures. Significant socio‐emotional changes dominated in early stages, while severe cognitive, behavioural, and physical deterioration shifted focus from predominant personality change to quality of life in later stages. Conclusions: Caregiver perspectives on target symptoms in bvFTD differ according to clinical stage and patient‐caregiver characteristics, with significant socio‐emotional changes characterizing early stages. These findings call for more appropriate tools and symptomatic treatments, as well as a personalized approach in treatment of bvFTD and a focus on early stage interventions in clinical trial design.